Influence Of Mechanical Properties On Load Sequence Effect And Fatigue Life Of Aluminium Alloy - Zakaria, Kamarul Ariffin; Ad Suhadak, Fadrah Hanim; Ali, Mohd Basri; Abdullah, S.; Ghazali, Mariyam Jameelah (Universiti Malaysia Pahang, Malaysia, 2017)
-